The Effectiveness of Islamic Religious Education in Enhancing Students' Religious Attitudes in the Digital Era at SMK Al Ishlah Cikarang Utara - Siti Ropiah; Idul Adhari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the effectiveness of Islamic Religious Education in enhancing students' religious attitudes in the digital era. With the advancement of technology and digital media, students now have increasingly broad access to diverse information, including content related to religious values. However, this convenience also brings new challenges, such as the spread of less credible information and content that may not align with religious values. Therefore, an effective educational approach is needed so that PAI can improve students' understanding, faith, and religious attitudes. This research uses a quantitative method with a survey approach. The study respondents consist of 10th and 11th-grade students from several high schools that have implemented technology-based PAI learning methods, such as digital learning applications and social media. Data was collected through questionnaires that included questions about changes in students' religious attitudes after participating in PAI learning in the digital era. Data analysis was conducted using statistical tests to determine the relationship between digital PAI learning and students' religious attitudes. The study results indicate that PAI learning using digital media has a significant positive impact on enhancing students' religious attitudes. Digital media helps students understand material in a more engaging, interactive, and accessible manner. Additionally, the use of digital platforms in PAI reinforces religious values amidst various influences from online content. However, its effectiveness heavily relies on teacher guidance and the careful selection of content to ensure material remains aligned with religious educational goals.